ANALISIS KEMAMPUAN NUMERASI PESERTA DIDIK DALAM MENYELESAIKAN SOAL MODEL ASESMEN KOMPETENSI MINIMUM DITINJAU DARI KECERDASAN EMOSIONAL - Dian Kurniawan; Yeni Heryani; Lukman Nurhakim (LPPM Universitas Advent Indonesia, 2024)
This study aims to describe students' numeracy skills in complete the question of the minimum competency assessment model that has intelligence emotional. The method used in this research is explorative method. The data collection technique consisted of an assessment model's numerical ability test minimum competence, distribution of emotional intelligence questionnaires, and interviews. The research subjects were selected from class VIII students at SMPN 17 Tasikmalaya totaling 22 students, based on the results of the numerical ability test of the assessment model minimum competence that meets the indicators of numeracy ability regardless the answer is right or wrong and the results of the emotional intelligence questionnaire are fulfilled categories of high, medium, low and students' ability to express ideas or ideas verbally or in writing for fluency in communication between researchers and research subjects. Based on the research results obtained that Subjects with high emotional intelligence are able to fulfill three indicators numeration skills. Subjects with moderate emotional intelligence are only capable fulfill two indicators of numeracy ability. Subject with intelligence low emotional is only able to fulfill two indicators of numeracy ability. Subjects with moderate and low emotional intelligence were only able to fulfill two the same indicators of numeracy abilities.